The press and citizenship education: Media reportage of political endorsements and electorate behaviour in Nigeria’s 2019 presidential election - Celestina Ongwayozi Audu (Ianna Journal of Interdisciplinary Studies, 2023)
Background: Political endorsement remains one of the global strategies that features visibly during electioneering campaigns. Such endorsements are usually communicated to the electorate through the media.